UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN KEMANGI (Ocimum sanctum L.) TERHADAP BAKTERI Staphylococcus epidermidis ATCC 12228 - Nur'Aini Purnamaningsih; Francisca Romana Sri Supadmi (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Indonesia is a tropical country that is rich in various types of plants that have the potential to be used in the health sector. Basil leaves (Ocimum sanctum L.) is a plant that has antibacterial potential. Antibacterial compounds are compounds that can inhibit bacterial growth. Objective: The objective of this study was to determine the antibacterial activity of basil leaf extract (Ocimum sanctum L.) with varying concentrations of 20%, 40%, 60%, 80% and 100%, and to determine the effective concentration of basil extract which has antibacterial activity against Staphylococcus epidermidis ATCC 12228. Methods: This research was conducted with laboratory experimental research method. Basil leaves ethanol extract was prepared by using maseration extraction method. The method used in the inhibitory test using diffusion of the disc with 5 samples in each treatment group. The sample consisted of treatment groups, ethanol extract of basil leaves with concentration of 20%, 40%, 60%, 80% and 100%. Results: Antibacterial test results showed that basil leaf extracts with various concentrations of 20%, 40%, 60%, 80% and 100% had antibacterial activity against Staphylococcus epidermidis ATCC 12228. The result of this study showed that ethanol extract of basil leaves with 20% concentration had inhibitory power of 10,23 mm, 40% of 10,32 mm, 60% by 10,58 mm, 80% by 13,37 mm, and 100% by 15,83 mm. Conclusion: Basil leaf extract concentrations 100% effective as an antibacterial against Staphylococcus epidermidis ATCC 12228 at 15,83 mm.